Elaboración del manual del sistema de Gestión Integral de Desechos Peligrosos y Bio-infecciosos para los Dispensarios del Seguro Social Campesino Zona 2 período 2019-2020. - Vallejo Pavón Juan Carlos, Juan Carlos (2020)
The purpose of this investigation was to identify the volume of sanitary waste produced in each of the Peasant Social Security dispensaries in zone 2, during the year 2019-2020. Planning Zone 2 is made up of three provinces: Napo, Pichincha and Orellana; The National Rural Social Security Directorate of the Ecuadorian Social Security Institute has 39 type 2 medical dispensaries, distributed in the three provinces. To carry out the historical analysis, three objectives were established: carry out the current diagnosis of the dispensaries, characterize the waste generated, generate a database to design the manual for the comprehensive management of sanitary waste and propose the implementation of the manual of comprehensive management for hazardous and bioinfectious waste. A quantity of sanitary waste of 2786.12 Kg / year was obtained, of which 336.6 Kg / year have been managed correctly, there is an average of 2449.52 Kg / year of waste delivered to recyclers, without any prior handling or treatment for final use. disposal, that is, only 12.1% of the waste is being properly treated and 87.9% is being disposed of in landfills. Based on these results, a waste management manual was prepared, both for non-hazardous or common waste, and for hazardous waste (infectious devices, chemical, pharmaceutical and medical, radioactive and others), all wastes containing organic substances and / or chemical, with CRTIB characteristics: Corrosive - Reactive - Toxic - Flammable - Bioinfectious. To comply with current Environmental Regulations, Ministerial Agreement No. 028, which replaces book VI of TULSMA, Section II, Comprehensive Management of Hazardous and / or Special Wastes, as a measure to mitigate environmental impact.